16+1 cooperation framework: Genesis, characteristics and prospect - Tianping Kong (Međunarodni Problemi)
The relations between China and Central and Eastern European countries (CEEC) have experienced different phases in the last 25 years. China’s new strategy toward CEE emerged in the last three years. It can be called the regional approach. The so-called regional approach to deal with Central and Eastern European countries can be regarded as a breakthrough in China’s policy towards Central and Eastern European countries. 16+1 cooperation framework has taken shape in the last three years. As China rediscovered different CEEC, CEEC rediscovered different China, common interests have drawn China and CEEC closer. The 16+1 cooperation framework is quite special, neither group nor international organization can encapsulate its characteristics. Equal partnership, loose institutionalization, comprehensive cooperation, multi-functional arrangement and well-planned framework are main characteristics. The 16+1 cooperation framework is a real novelty in international relations. The emergence of 16+1 framework arises from both common political will to cooperation and mutual demand for closer economic links. The 16+1 framework has to face several challenges.